ENT 530 Business Plan : Cutthings Sdn Bhd / Siti Nur Afiqah Ahmad Sabri ... [et al.] - Ahmad Sabri, Siti Nur Afiqah; Kamisan, Nurul Nadiah; Khalilullah, Nur Izatul Amirah; Muhamad Zakir, Nurul Fatin Farhanis; Husni, Siti Aisyah; Zulkifli, Nurizah Iylia (2019)
The current trend towards an increase in innovative products presents an opportunity for CutThings SDN BHD to penetrate the market. We are on the brink of penetrating a lucrative market in a rapidly growing industry. An opportunity for success exists because the modern lifestyle is growing at a rapid pace annually especially in Malaysia. CutThings SDN BHD take advantage of this growth and moderate competition in the city travel portion of the industry.